Pengaruh Seleksi dan Penempatan Terhadap Kinerja Karyawan PT. Sukses Mitra Sejahtera Kab. Kediri - Mutya Khanza Santovi (Universitas Islam Kadiri, 2022)
This research aims to determine the effect of selection and placement on employee performance at Sukses Mitra Sejahtera, PT in Kediri district. The population in this research amounted to 704 people, the sampling technique used the Simple Random Sampling and obtained a sample of 88 people. This research uses descriptive statistical analysis method with hypothesis testing using SPSS version 22 software program. Based on the results of the F test, it is proven that the variable selection and placement simultaneously affect employee performance, indicated by a significant value of 0.000 <0.05. The t-test shows that the selection variable has a partial effect on employee performance. This is indicated by the significant value for the selection variable 0.008 <0.05 and for the placement variable it has a partial effect on employee performance. This is evidenced by a significance level of 0.000 < 0.05. The coefficient of determination test shows that the value (R Square) is 0.428. It means that the effect of selection and placement variables on employee performance is 42.8%. Keywords: Selection, Placement, Employee Perfomance